Предмет: Алгебра,
автор: Аноним
Упростите выражение:
1)(x-2)в кубе - (x+2)в кубе
2)(a+3)в кубе - (a-1)в кубе-12aв квадрате
Ответы
Автор ответа:
0
1) (х-2)³-(х+2)³=х³-6х²+12х-8-х³-6х²-12х-8=-12х²-16
2) (а+3)³-(а-1)³-12а²=а³+9а²+27а+27-а³+3а²-3а+1-12а²=24а+28
2) (а+3)³-(а-1)³-12а²=а³+9а²+27а+27-а³+3а²-3а+1-12а²=24а+28
Автор ответа:
0
Похожие вопросы
Предмет: Музыка,
автор: banbanbanban33
Предмет: Математика,
автор: 19941991nusu
Предмет: Математика,
автор: sabinasabina3121
Предмет: Математика,
автор: zzzБОЛЬШОЙzzz
Предмет: Математика,
автор: Амир95